Legal protection of trees and shrubs in the Czech lands: review article - Radecki, Wojciech (Przegląd Prawa Rolnego, 2025)
This article summarises the key theses contained in Milan Šimandl’s monograph on the development of legal protection for trees and shrubs in the Czech lands. It considers the extensive Czech legal literature on this topic, as well as makes brief comparative remarks relating to Polish law.